2017
DOI: 10.1177/2168479017706526
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Seamless Design for Establishing Pharmacokinetic and Efficacy Equivalence in Developing Biosimilars

Abstract: This proposal provides appealing advantages, such as a shorter time period, additional cost savings, and a smaller number of patients required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A simulation study investigating a seamless phase II/ III trial with promising zone design suggested some appealing advantages over classical designs including time, cost and sample size savings, which could speed up the development of biosimilars [17]. Additionally, it has been suggested that promising zone designs could be particularly useful in early-stage exploratory studies where very little is known about the treatment effect [18], and in clinical trials of rare diseases [19].…”
Section: Strengthsmentioning
confidence: 99%
“…A simulation study investigating a seamless phase II/ III trial with promising zone design suggested some appealing advantages over classical designs including time, cost and sample size savings, which could speed up the development of biosimilars [17]. Additionally, it has been suggested that promising zone designs could be particularly useful in early-stage exploratory studies where very little is known about the treatment effect [18], and in clinical trials of rare diseases [19].…”
Section: Strengthsmentioning
confidence: 99%
“…Pan et al 10 proposed a Bayesian group sequential design that integrates historical information through the calibrated power prior approach. Uozumi and Hamada 11 developed an adaptive seamless PK and efficacy design to combine the tests of PK parameters and efficacy. Weiss et al 12 proposed to incorporate prior information from the historical data of the reference product, and the results from in vitro and phase I PK/PD study of the biosimilar.…”
Section: Introductionmentioning
confidence: 99%